Synchronous multiple primary cancers involving rectal cancer and pelvic classical hodgkin lymphoma: the first case report - Liu, Shiyue; Li, Hong; Dong, Youhong; Zhang, Dongdong (Frontiers in Oncology, 2023)
Multiple primary cancers (MPC) are characterized by the presence of synchronous and metachronous occurrence of two or more distinct histological tumor types. In this study, an exceptional clinical case was presented, demonstrating the coexistence of rectal adenocarcinoma and pelvic classical Hodgkin lymphoma (cHL). A 65-year-old male patient with a 2-year history of persistent mucous bloody stools was admitted to our hospital. Colonoscopy and subsequent biopsy confirmed the diagnosis of rectal adenocarcinoma. The patient underwent laparoscopic abdominoperineal resection of the rectum and regional lymph node dissection. Postoperative histopathological analysis not only substantiated the presence of rectal adenocarcinoma, but also unexpectedly identified pelvic lymph nodes harboring the features of cHL.